Determinants of Capital Structure: Empirical Evidence from Malaysia - Tleubayev, Adilbek (2009)
This study investigates characteristics of capital structure and use of financing for Malaysian listed companies for the period of 2001-2008. In purpose of identifying the difference of Malaysian capital mix from other countries and testing applicability of major theoretical models, leverage variables were examined using series of firm characteristics including: growth, profitability, size, tangibility, investment opportunities and risk. The results that as in other countries, leverage in Malaysian companies increases with tangibility and size, but decreases with profitability. It was also found that different from findings in other markets, leverage increases with business risk, while growth and investment opportunities have negative impact on short-term debt and positive on long-term debt. The results generally support trade-off and pecking order propositions avocated in theoretical models.